Taking Language out of the Equation: The Assessment of Basic Math Competence Without Language - Greisen, Max; Hornung, Caroline; Baudson, Tanja G.; Muller, Claire; Martin, Romain; Schiltz, Christine (Frontiers in Psychology, 2018)
While numerical skills are fundamental in modern societies, some estimated 5-7% of children suffer from mathematical learning difficulties that need to be assessed early to ensure successful remediation. Universally employable diagnostic tools are yet lacking, as current test batteries for basic mathematics assessment are based on verbal instructions. However, prior research has shown that performance in mathematics assessment is often dependent on the testee’s proficiency in the language of instruction which might lead to unfair bias in test scores. Furthermore, language-dependent assessment tools produce results that are not easily comparable across countries. Here we present results of a study that aims to develop tasks allowing to test for basic math competence without relying on verbal instructions or task content. We implemented video and animation-based task instructions on touchscreen devices that require no verbal explanation. We administered these experimental tasks to two samples of children attending the first grade of primary school. One group completed the tasks with verbal instructions while another group received video instructions showing a person successfully completing the task. We assessed task comprehension and usability aspects both directly and indirectly. Our results suggest that the nonverbal instructions were generally well understood as the absence of explicit verbal instructions did not influence task performance. Thus we found that it is possible to assess basic math competence without verbal instructions. It also appeared that in some cases a single word in a verbal instruction can lead to the failure of a task that is successfully completed with nonverbal instruction. However, special care must be taken during task design because on rare occasions nonverbal video instructions fail to convey task instructions as clearly as spoken language and thus the latter do not provide a panacea to nonverbal assessment. Nevertheless, our findings provide an encouraging proof of concept for the further development of nonverbal assessment tools for basic math competence.